2017
DOI: 10.24181/tarekoder.369470
|View full text |Cite
|
Sign up to set email alerts
|

Arı Ürünleri Tüketicilerinin Genel Özellikleri ve Tüketim Tercihleri: Çanakkale İli Örneği

Abstract: ÖzetArı ürünler beslenme ve sağlıklı b r yaşam sürdüreb lmek ç n gıda tüket m terc hler nde g derek öneml hale gelen ürünler arasındadır. Bu çalışmanın amacı arı ürünler tüket c ler n n genel özell kler n n ve tüket m terc hler n n ortaya konulmasıdır. Bu amaçla öneml b r üret m ve tüket m merkez olan Çanakkale l nde 175 tüket c le yüz yüze anket yapılmıştır. Çalışma sonuçlarına göre arı ürünler tüket c ler n n yarısından fazlası kadındır. Tüket c ler n büyük çoğunluğu orta yaş grubunda, l se veya ün vers te m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
11
0
5
Order By: Relevance
“…The average annual consumption of pollen, royal jelly, and the propolis are 34.74 gr year -1 , 12.37 gr year -1 and 12.96 gr year -1, respectively. In another study, Niyaz and Demirbaş (2017) found that the responders consume 14.87 gr pollen, 3.52 gr propolis, 0.98 gr royal jelly per month. In addition, the most commonly consumed bee product is honey, whereas the consumption frequency of other bee products was quite low.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The average annual consumption of pollen, royal jelly, and the propolis are 34.74 gr year -1 , 12.37 gr year -1 and 12.96 gr year -1, respectively. In another study, Niyaz and Demirbaş (2017) found that the responders consume 14.87 gr pollen, 3.52 gr propolis, 0.98 gr royal jelly per month. In addition, the most commonly consumed bee product is honey, whereas the consumption frequency of other bee products was quite low.…”
Section: Resultsmentioning
confidence: 93%
“…In another study, Baki et al (2017) found that annual per capita honey consumption is 1.55 kg, and approximately half of this honey consumption is composed of pine honey. On the other hand, Niyaz and Demirbaş (2017) found that consumers living in Canakkale province consume comb honey around 44.35 gr month -1 and liquid honey about 315.35 gr month -1 . Schifani et al (2016) found that the percentage of responders consuming honey rarely is around 29%, whereas the proportion of responders consuming honey every day is about 18%.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations